Prophylaxis against venous thromboembolism in perimenopausal women - Sajdak, Stefan; Moszyński, Rafał (Menopause Review/Przegląd Menopauzalny, 2008)
Venous thromboembolism in perimenopausal women is a cause of serious clinical consequences such as deep vein thrombosis or pulmonary embolism. These complications in their early stage are usually asymptomatic and after clinical manifestation their treatment is much more difficult, which is a good reason for prophylaxis. The most effective and economical method for prevention of serious venous thromboembolic complications is properly administrated prophylactic activity. In perimenopausal women anti-thrombotic prophylaxis is especially important because of the presence of numerous, usually cumulated risk factors of venous thromboembolism. This concerns age of the patient, obesity, hormonal treatment, indications for surgery, immobilization and higher risk of some malignant diseases in this period. Good prophylaxis should be assessed in respect of effectiveness and safety of various methods and their costs. Pharmacological prophylaxis should be assessed for dose and duration of treatment. Effective prophylaxis is possible after precise analysis of all risk factors of thromboembolic complications in perimenopausal women. This article discusses the most important risk factors and indications for venous thromboembolism prophylaxis in perimenopausal women.